2010
DOI: 10.1007/s11837-010-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and analysis of Porous, Brittle solid structures by X-ray micro computed tomography

Abstract: City, Utah 84112 USA. Dr. Miller can be reached at (801) 581-5160; fax (801) 581-4937; e-mail Jan. Miller@utah.edu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Work has also been published on the use of X-ray CT for characterizing polymer foams and closed-celled metal foams [28,31,[35][36][37][38][39]. The current approach is to obtain geometric data for several Duocel® Al-6106-T6 open-cell metal foam samples of varying porosities using X-ray CT, and to use the results for a comparison to idealized geometries.…”
Section: Methodsmentioning
confidence: 99%
“…Work has also been published on the use of X-ray CT for characterizing polymer foams and closed-celled metal foams [28,31,[35][36][37][38][39]. The current approach is to obtain geometric data for several Duocel® Al-6106-T6 open-cell metal foam samples of varying porosities using X-ray CT, and to use the results for a comparison to idealized geometries.…”
Section: Methodsmentioning
confidence: 99%
“…Marker-controlled watershed segmentation has been applied to 3D µCT images for several analyses by Miller et al [22,89,90]. 3D watershed segmentation has been applied to different types of µCT image analysis, including coal washability analysis [89], air bubble sizes [90], as well as analysis of particle beds [22].…”
Section: Region Growingmentioning
confidence: 99%
“…Marker-controlled watershed segmentation has been applied to 3D µCT images for several analyses by Miller et al [22,89,90]. 3D watershed segmentation has been applied to different types of µCT image analysis, including coal washability analysis [89], air bubble sizes [90], as well as analysis of particle beds [22]. Wang et al [22] identified that 3D watershed segmentation works best for mineral particles greater than the scale parameter (particle size/voxel size ratio of 30) and density lower than 4.0 g/cc.…”
Section: Region Growingmentioning
confidence: 99%
“…Pyrophyllite was selected as a reasonable standard that has no porosity to compare with consolidated HNTs. The ratio of X-ray attenuation for consolidated HNTs to pyrophyllite is reported as the micro-XCT estimated porosity for consolidated HNT, similar to a previous study on porous and brittle solid structures [17]. To validate the total porosity estimated by X-ray attenuation, the He porosimetry of natural consolidated HNTs was measured using an Ultra-Pore 300TM porosimeter manufactured by Core Laboratories.…”
Section: Porosity By X-ray Attenuation In Micro-x-ray Computed Tomography (Micro-xct)mentioning
confidence: 62%